Characteristics and short-term outcomes of young women with acute myocardial infarction in Malaysia: a retrospective analysis from the Malaysian National Cardiovascular Database registry - Venkatason, Padmaa; Zubairi, Yong Zulina; Zaharan, Nur Lisa; Wan Ahmad, Wan Azman; Hafidz, Muhammad Imran Abdul; Ismail, Muhammad Dzafir; Hadi, Mohd Firdaus; Md Sari, Norashikin; Zuhdi, Ahmad Syadi Mahmood (BMJ Publishing Group, 2019)
Objective Young women form a minority but an important group of patients with acute myocardial infarction (MI) as it can potentially cause devastating physical and socioeconomic impact. This study was aimed to investigate the characteristics and outcomes of young women with MI in Malaysia. Design This is a retrospective analysis of women with ST-elevation MI (STEMI) and non-STEMI (NSTEMI) from 18 hospitals across Malaysia using the Malaysian National Cardiovascular Database registry-acute coronary syndrome (NCVD-ACS). Participants Women patients diagnosed with acute MI from year 2006 to 2013 were identified and divided into young (age ≤ 45, n=292) and older women (age >45, n=5580). Primary outcome measure Comparison of demographics, clinical characteristics and in-hospital management was performed between young and older women. In-hospital and 30-day all-cause mortality were examined. Results Young women (mean age 39±4.68) made up 5% of women with MI and were predominantly of Malay ethnicities (53.8%). They have a higher tendency to present as STEMI compared with older women. Young women have significantly higher rates of family history of premature coronary artery disease (CAD) (20.5% vs 7.8% p<0.0001). The prevalence of risk factors, such as hypertension, diabetes and dyslipidaemia was high in both groups. The primary reperfusion strategy was thrombolysis with no significant differences observed in the choice of intervention for both groups. Other than aspirin, rates of prescriptions for evidence-based medications were similar with >80% prescribed statins and aspirin. The all-cause mortality rates of young women were lower for both in-hospital and 30 days, especially in those with STEMI with adjusted mortality ratio to the older group, was 1:9.84. Conclusion Young women with MI were over-represented by Malays and those with a family history of premature CAD. Preventive measures are needed to reduce cardiovascular risks in young women. Although in-hospital management was similar, short-term mortality outcomes favoured young compared with older women. © © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.